Development of a critical thinking skills assessment instrument for students on diffusion and osmosis subject - Abidin, Zaenal; Fatimatuzzaro, Fatimatuzzaro (Universitas Wiralodra, 2025)
Critical thinking is a crucial 21st-century skill that enables students to analyze information, evaluate arguments, and make logical decisions. However, assessments in Biology education often focus more on factual knowledge rather than higher-order thinking skills. This research aimed to develop an assessment instrument for measuring students' critical thinking skills in diffusion and osmosis. This study used the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research was conducted with 46 students from the XI MIPA class at MA Nurul Huda Munjul. The assessment instrument consists of multiple-choice questions designed to evaluate six components of critical thinking: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Validation results indicate that 20 out of 24 test items are valid, while four require revision or replacement. Reliability testing using the split-half method shows a coefficient of 0.672, which falls into the moderate reliability category and is still acceptable for educational assessment purposes. The developed instrument provides teachers with a tool to evaluate students’ critical thinking skills better and tailor their teaching strategies accordingly. This study contributes to improving Biology education by promoting a more contextual and problem-solving-based approach to assessment.